2021
DOI: 10.3389/frsc.2021.713977
|View full text |Cite
|
Sign up to set email alerts
|

Coping With Crisis: Green Space Use in Helsinki Before and During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has encouraged a deeper exploration about how people deal with crisis. This paper presents one of the first pre- and during-pandemic assessments of urban green infrastructure (UGI) use across the same individuals with the aim of better understanding how people's use of different types of urban green and blue spaces changed during the pandemic. A baseline Public Participation GIS survey (N = 1,583 respondents) conducted in August 2018 was followed up in May 2020 (N = 418 identical responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 56 publications
4
39
1
Order By: Relevance
“…Unlike several other nature pandemic studies [23,24,26,53], on average, our participants did not report spending significantly more time in nature. They did report spending more time in green spaces, specifically, and they also indicated that they appreciated nature more, feared it less, and noticed wildlife slightly more as a result of the pandemic.…”
Section: Discussioncontrasting
confidence: 91%
“…Unlike several other nature pandemic studies [23,24,26,53], on average, our participants did not report spending significantly more time in nature. They did report spending more time in green spaces, specifically, and they also indicated that they appreciated nature more, feared it less, and noticed wildlife slightly more as a result of the pandemic.…”
Section: Discussioncontrasting
confidence: 91%
“…During the peak of the pandemic, prolonged home confinement because of travel restrictions was a source of motivation that influenced city dwellers' behaviour and preference for parks and open spaces [19]. Several studies also reported a general increase in green space use during the pandemic [20][21][22][23]. According to an Australian study, females were more likely than men to adjust their green space visiting frequency during the pandemic, and they also placed a greater value on green spaces for social and familial relationships, as well as spiritual reasons [24].…”
Section: Introductionmentioning
confidence: 99%
“…Ugolini et al [ 9 ] also pointed to the importance of diverse urban greenspace and related means of transportation: people walking to small urban gardens nearby (e.g., in Italy) or tree-lined streets (e.g., in Spain, Israel), and people traveling by car to green areas outside the city (e.g., in Lithuania). Similarly, Korpilo et al [ 41 ] showed that Helsinki residents were more likely to visit greenspaces closer to their homes for recreation during the pandemic than before the pandemic. Residents were more likely to visit nearby residential areas with high tree cover density, underscoring the importance of urban forests and tree-rich parks in their neighborhoods.…”
Section: Discussionmentioning
confidence: 99%